THEORETICAL BASIS OF DETERMINATION OF FRAUD CASES THROUGH AUDIT INSPECTIONS (Marketing Journal, 2025)
This article outlines the theoretical foundations for identifying fraud cases through audits. In particular, the concept of fraud, fraud cases, and the risk factors that cause them, as well as the analytical procedures used in identifying fraud cases relat ed to current assets, were classified, and conclusions were formulated.
Keywords: fraud; audit; auditor; audit procedures; analytical procedures; asset; current assets